Design and development frequency reconfigurable microwave filter for wireless application - Khyati Chavda; Ashish Sarvaiya (Institute of Advanced Engineering and Science, 2023)
This paper presents a novel reconfigurable bandpass filter with three reconfigurable states used for C band wireless applications. The frequency reconfigurable is achieved using the combination of a different microstrip coupled resonator structure and switching device as PIN diodes. The open-loop filter structure provides three narrow band states at 5.1, 5.2, and 5.8 GHz. The frequency reconfiguration is obtained without compromising performances. The compact size of the proposed designed along with the targeted frequency bands at lower wireless local area network (WLAN) (5.1, 5.2 GHz), and worldwide interoperability for microwave access (WiMAX) (5.8 GHz) applications. The prototype is constructed on an RT duroid 5880 substrate and tested for validation in vector network analyzer (VNA). The designed filter provides excellent selectivity and good rejection at desired resonant frequencies.